Mozambique Cashew Reforms Revisited - Aksoy, M. Ataman; Yagci, Fahrettin (2012)
Cashew policy reforms in Mozambique have been controversial. They are often invoked by critics as an illustration of how agricultural policy reforms supported by international financial institutions may fail to have their intended effects. This paper revisits the reforms and their outcomes almost two decades later. While the reforms resulted in higher producer prices and an increase in output, lack of consensus on the specifics of the reforms and associated non-price support arrangements created a situation in which the sector was not able to withstand international price shocks that ultimately led to a collapse of both the processing industry and cashew production. Non-price support by donors improved the efficiency of the processing industry but this was not complemented by an expansion in cashew nut supply as such support did not extend to smallholder cashew producers. For the reforms to have had their intended results, greater investment in -- and support to -- smallholder production was needed to increase yields and overall output. Such a more comprehensive approach to cashew policy reform would have required a greater focus on achieving consensus on the causes of the cashew sector's problems and agreement by all stakeholders on a common institutional framework for pricing and non-price support.